Growth of leopard flower (Belamcanda chinensis) with humics acids in nursery garden (Research, Society and Development, 2021)
Humic acids constitute a fraction of organic matter that either has direct effects on the growth and development of ornamental plants. The present study aimed to evaluate the differential growth of the leopard flower (Belamcanda chinensis) from the application of humic acids extracted from poultry litter (HAPL) and bovine manure (HABM) during the nursery garden phase. The seeds were immersed in solutions of 0, 10, 20, 30 and 40 mmol L-1 of C in HAPL and in the same way for HABM. After 150 days, the plants were collected and measured the number of leaves, plant height, fresh matter of the aerial part, dry matter of the root, total fresh matter, and dry matter of the aerial part, dry matter of the root and total dry matter. The use of the correct concentration of humic acids stimulates the growth and accumulation of total dry material in the leopard plant in the order of 33% to 58% for HAPL and HABM respectively.